2018
DOI: 10.1177/1473871618799500
|View full text |Cite
|
Sign up to set email alerts
|

On the readability of leaders in boundary labeling

Abstract: External labeling deals with annotating features in images with labels that are placed outside of the image and are connected by curves (so-called leaders) to the corresponding features. While external labeling has been extensively investigated from a perspective of automatization, the research on its readability has been neglected. In this article, we present the first formal user study on the readability of leader types in boundary labeling, a special variant of external labeling that considers rectangular i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 45 publications
(53 reference statements)
0
12
0
Order By: Relevance
“…However, their approaches have asymptotically high running times, e.g., for the one-sided case they obtained a running time of O(n 11 ) and for the two-sided case they obtained a running time of O(n 27 ) when minimizing the total leader length. Barth et al [BGNN18] used an integer linear programming formulation to create one-sided boundary labelings with straight-line leaders (Section 5.2.5). They used these labelings in a user study on the readability of different leader types.…”
Section: Detailed Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, their approaches have asymptotically high running times, e.g., for the one-sided case they obtained a running time of O(n 11 ) and for the two-sided case they obtained a running time of O(n 27 ) when minimizing the total leader length. Barth et al [BGNN18] used an integer linear programming formulation to create one-sided boundary labelings with straight-line leaders (Section 5.2.5). They used these labelings in a user study on the readability of different leader types.…”
Section: Detailed Discussionmentioning
confidence: 99%
“…Straight-line leaders are the simplest way to establish the visual association between features and their external labels. Further, they can be easily traced by the reader [BGNN18]. We first give an overview on the current research (Section 4.1.1) and then discuss the individual papers concerning their particular contributions (Section 4.1.2).…”
Section: Straight-line Leadersmentioning
confidence: 99%
“…This style of leader line was chosen as opposed to orthogonal leaders (i.e., leaders comprising one horizontal and one vertical segment). While in general, orthogonal leaders have been observed to have great legibility [6], we have found that diagonal lines stand out better amidst the clutter of other marks in an equation (M6).…”
Section: Equation Diagramsmentioning
confidence: 57%
“…We conduct a post-hoc analysis of pairwise contrasts to quantify the differences in mean effect of interface on y under the GLMM (and controlling for question). Two-sided t-tests for pairwise contrasts are computed using the emmeans R package, 6 and results are shown in Table 1.…”
Section: A2 Details Of Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation